Out of sight : the rise of African American popular music, 1889-1895 - Abbott, Lynn, 1946- (American made music series., 2002)
The early 1890s witnessed over a thousand lynchings of African Americans. At the same time this brutalised community gave birth to the phenomenon of ragtime & the popular entertainment industry. 'Out of Sight' examines this apparent contradiction.